The Effectiveness of School Environment-Based Inquiry Model in the Ecosystem Material Towards Critical Thinking Ability and Environmental Caring Attitudes of High School Students - Utami, Annastesia Berliyan; Widiyaningrum, Priyantini (FMIPA UNNES, 2019)
The purpose of this study is to analyze the effectiveness of the school environment-based inquiry model in the ecosystem material towards critical thinking ability and environmental caring attitude of high school students. This study uses Pre-Experiment Design with research design of One Group Pretest-Posttest Design. The sample of this study was grade X IPA 5 and X IPA 6 SMA Negeri 1 Slawi. The results of this study indicate that the result of the N-gain test of critical thinking ability and the attitude of caring for the environment is in the medium category. The result of classical learning completeness reach 100% of students complete. Students' critical thinking ability shows 100% of students meet critical and very critical criteria. The environmental caring attitude of the students shows that 100% of students fulfill the criteria of care and absolutely care. Students’ responses to learning show good criteria in each statement. Conclusion in this study is that the school environment-based inquiry model in the ecosystem material is effective towards critical thinking ability and environmental caring attitude of grade X students of SMA Negeri 1 Slawi.